Global environmental changes negatively impact temperate seagrass ecosystems. Issue 12 (19th December 2019) - Perry, Diana; Staveley, Thomas; Deyanova, Diana; Baden, Susanne; Dupont, Sam; Hernroth, Bodil; Wood, Hannah; Björk, Mats; Gullström, Martin
Abstract: The oceans are increasingly affected by multiple aspects of global change, with substantial impacts on ecosystem functioning and food‐web dynamics. While the effects of single factors have been extensively studied, it has become increasingly evident that there is a need to unravel the complexities related to a multiple stressor environment. In a mesocosm experimental study, we exposed a simplified, multi‐trophic seagrass ecosystem (composed of seagrass, two shrimp species, and two intermediate predatory fish species) to three global change factors consisting of simulated storm events (Storms), heat shocks (Heat), and ocean acidification (OA), and the combination of all three factors (All). The most striking result indicated that when all factors were combined, there was a negative influence at all trophic levels, while the treatments with individual factors revealed species‐specific response patterns. It appeared, however, that single factors may drive the multi‐stressor response. All single factors (i.e., Storms, Heat, and OA) had either negative, neutral, or positive effects on fish and shrimp, whereas no effect was recorded for any single stressor on seagrass plants. The findings demonstrate that when several global change factors appear simultaneously, they can have deleterious impacts on seagrass ecosystems, and that the nature of factors and food‐web composition may determine the sensitivity level of the system. In a global change scenario, this may have serious and applicable implications for the future of temperate seagrass ecosystems.